MODULATING GRAMMAR THROUGH MODALITY: A DISCOURSE APPROACH - Gonzálvez García, Francisco (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This paper argues for a dynamic, discourse-based approach to modality which departs from the traditional, monolithic account of modality in a number of interesting respects: (i) modality is characterized as conveying the speaker’s involvement in the propositional content of a given utterance (either in the form of agency or subjectivity) (ii) modality can be said to ramify across the whole lexico-grammatical architecture of the language, (iii) many of the meanings usually ascribed to individual modal verbs are in fact derived either from the verb’s sentential environment or from some wider context of utterance, and (iv) modal meaning in discourse can be said to arise out of the interaction of two closely connected layers of meaning: one embracing the inherent linguistic meaning of the modal verb in conjunction with that of other neighbouring modal devices, and another concerned with principles connected with politeness and face-saving strategies